Examinating The Effect of Covid-19 on The Efficient Market Hypothesis (EMH) Anomaly of The Islamic Stock Index in Indonesia - Purwanto Widodo (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This study aims to determine whether Covid-19 affects the return pattern of the Jakarta Islamic Index (JII) and whether the JII return is efficient in accordance with the Efficient Market Hypothesis (EMH). To ensure that the data analysis was in accordance with the objectives, samples were taken from January 1, 2008, to June 28, 2024, with ARCH-GARCH analysis so that the results were consistent and not robust. The findings of this research are as follows: JII returns are efficient because there is no Covid-19 effect and EMH anomaly, where there is no evidence of the day-of-the-week effect, Monday Effect, Friday Effect, or week four effect. In addition, the appropriate model is asymmetric EGARCH (1,1) with non-normal error term distribution. These findings have implications for investors, policy makers, and researchers interested in the performance and behavior of the Islamic stock market, so that in analyzing the stock market more strengthen the fundamental analysis of the company.